Structural diversity of nuptial pads in Phyllomedusinae (Amphibia: Anura: Hylidae) - Luna, María Celeste (2012)
We studied the morphological variation of the nuptial pads using light microscopy and scanning electron microscopy (SEM) in 26 species of phyllomedusines (Anura: Hylidae), representing the five currently recognized genera. All phyllomedusines have single nuptial pads with dark colored epidermal projections (EPs). Spine-shaped EPs occur in Cruziohyla calcarifer, Phrynomedusa appendiculata and in one species of Phasmahyla. The other species have roundish EPs. The density of the EPs on the pad is variable. Species in the Phyllomedusa hypochondrialis Group have EPs with a density that varies between 764 ± 58/mm 2 and 923 ± 160/mm 2. In all other studied species (including the Phyllomedusa burmeisteri and Phyllomedusa perinesos groups, Phyllomedusa camba, Phyllomedusa boliviana, Phyllomedusa sauvagii, Phyllomedusa bicolor, and Phyllomedusa tomopterna) the density of EPs varies between 108 ± 20/mm 2 and 552 ± 97/mm 2. Pores were observed with SEM in C. calcarifer, Agalychnis lemur, Agalychnis moreletii, but its presence is confirmed through histological sections on several other species. Its visibility using SEM seems to be related with the level of separation between adjacent EPs. The pores in the four studied species of Agalychnis are shown with SEM and histological sections to have a characteristic epidermal rim, that is absent in the otherphyllomedusines. Unlike most previous reports on breeding glands, those of phyllomedusines are alcian blue positive, indicating the presence of acidic mucosubstances on its secretions.